Factors Influencing Consumers’ Purchase Intention Towards Green Home Appliances - Teoh, Chen Wei; Khor, Kok Chin; Wider, Walton (Frontiers in Psychology, 2022)
The main purpose of this study is to investigate the effect of after sales service (ASS), brand equity (BE), environmental awareness (EA), and product pricing (PP) towards consumer purchase intention (CPI) of green home appliance. Data were collected from 150 Penang, Malaysia citizen who were age from 18 to 60 via convenient sampling method analysed using partial least square structure equation modelling (SmartPLS). Results indicated that BE, EA, and PP has significant effect on CPI of green home appliance brand. However, ASS do not have significant effect on CPI on green home appliance brand. This research helps home appliance manufacturer to better design marketing promotions, considering the consumers focus on BE, EA, and pricing. In addition, this study provides consumer insight for the government agency to construct better policy in order to increase the green home appliance penetration rate among citizens.